Challenges in recruiting and retaining adolescents with abuse-related posttraumatic stress disorder: lessons learned from a randomized controlled trial - Anna Vogel; Hannah Comtesse; Rita Rosner (BMC, 2020)
Abstract Background Research on effective recruitment and retention strategies for adolescents and young adults suffering from posttraumatic stress disorder is scarce. The aim of the current study was to provide data on recruitment sources, barriers, and facilitators for participation in a randomized controlled trial for young individuals with histories of sexual and/or physical abuse. Methods Study participants aged 14 to 21 were asked to complete a checklist on individual sources of recruitment, barriers, and facilitators for participation in the trial. Fifty-three out of the 80 study participants who were contacted completed the checklist (66.3%). Results Most respondents reported multiple recruitment sources, with online and media advertising search strategies indicated most frequently (45.4% of all mentions), followed by practitioner-referred sources (38.7%). Respondents' reported barriers included additional demands of the trial (60.3%), followed by distress caused by having to talk about painful topics (15.5%). The most frequently indicated facilitators were the organizational setting (55.1%) and monetary incentives (22.2%), followed by social support (12.0%) and non-monetary incentives (10.2%). No significant differences were observed between adolescent and young adult respondents with the exception that adolescents reported significantly more frequently that they had learned about the trial from their caregiver. Conclusions Our findings permit the formulation of recommendations for planning and conducting trials with this clientele. Future research is needed on how specific barriers can be effectively overcome.